Role of Outer Membrane Vesicles From Helicobacter pylori in Atherosclerosis - Wang, Na; Zhou, Faying; Chen, Caiyu; Luo, Hao; Guo, Jingwen; Wang, Wei; Yang, Jian; Li, Liangpeng (Frontiers in Cell and Developmental Biology, 2021)
Infection is thought to be involved in the pathogenesis of atherosclerosis. Studies have shown the association between helicobacter pylori (H. pylori) and coronary artery disease. It is interesting to find H. pylori DNA and cytotoxin-associated gene A (CagA) protein in atherosclerotic plaque. Outer membrane vesicles (OMVs), secreted by H. pylori, exert effects in the distant organ or tissue. However, whether or not OMVs from H. pylori are involved in the pathogenesis of atherosclerosis remains unknown. Our present study found that treatment with OMVs from CagA-positive H. pylori accelerated atherosclerosis plaque formation in ApoE−/− mice. H. pylori-derived OMVs inhibited proliferation and promoted apoptosis of human umbilical vein endothelial cells (HUVECs), which was also reflected in in vivo studies. These effects were normalized to some degree after treatment with lipopolysaccharide (LPS)-depleted CagA-positive OMVs or CagA-negative OMVs. Treatment with H. pylori-derived OMVs increased reactive oxygen species (ROS) levels and enhanced the activation of nuclear factor-κB (NF-κB) in HUVECs, which were reversed to some degree in the presence of a superoxide dismutase mimetic TEMPOL and a NF-κB inhibitor BAY11-7082. Expressions of interleukin-6 (IL-6) and tumor necrosis factor alpha (TNF-α), two inflammatory factors, were augmented after treatment with OMVs from H. pylori. These suggest that H. pylori-derived OMVs accelerate atherosclerosis plaque formation via endothelium injury. CagA and LPS from H. pylori-OMVs, at least in part, participate in these processes, which may be involved with the activation of ROS/NF-κB signaling pathway. These may provide a novel strategy to reduce the incidence and development of atherosclerosis.